2010
DOI: 10.1186/1476-511x-9-43
|View full text |Cite
|
Sign up to set email alerts
|

Differential alterations of the concentrations of endocannabinoids and related lipids in the subcutaneous adipose tissue of obese diabetic patients

Abstract: BackgroundThe endocannabinoids, anandamide and 2-AG, are produced by adipocytes, where they stimulate lipogenesis via cannabinoid CB1 receptors and are under the negative control of leptin and insulin. Endocannabinoid levels are elevated in the blood of obese individuals and nonobese type 2 diabetes patients. To date, no study has evaluated endocannabinoid levels in subcutaneous adipose tissue (SAT) of subjects with both obesity and type 2 diabetes (OBT2D), characterised by similar adiposity and whole body ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 40 publications
5
52
0
1
Order By: Relevance
“…Liver transcriptomic and proteomic analyses related to the ECS also supported a stimulatory effect of HFD on EC tone, as indicated by the marked increase in NAPE-PLD and CB1R expression along with the concomitant decrease in FAAH expression and activity. However, an important finding concerns EC levels in the inguinal AT, which were lowered in all groups after HFD challenge, which is in agreement with previous works (47,49) concerning the impact of HFD on adipose depots of both rodents and humans. Because leptin and insulin were strongly increased after HFD challenge, it might be suggested that the decrease in SCAT EC levels is due to the action of these hormones on EC production, as previously shown (50,51).…”
Section: Discussionsupporting
confidence: 91%
“…Liver transcriptomic and proteomic analyses related to the ECS also supported a stimulatory effect of HFD on EC tone, as indicated by the marked increase in NAPE-PLD and CB1R expression along with the concomitant decrease in FAAH expression and activity. However, an important finding concerns EC levels in the inguinal AT, which were lowered in all groups after HFD challenge, which is in agreement with previous works (47,49) concerning the impact of HFD on adipose depots of both rodents and humans. Because leptin and insulin were strongly increased after HFD challenge, it might be suggested that the decrease in SCAT EC levels is due to the action of these hormones on EC production, as previously shown (50,51).…”
Section: Discussionsupporting
confidence: 91%
“…[6][7][8] Recent investigations of the ECs in SAT by Annuzzi el al. 34 in a small sample of obese and lean individuals did not detect significant difference between lean and obese subjects, whereas obese with type 2 diabetes had significant higher AEA and lower 2-AG levels. Concerning the lean and obese individuals their findings were in good agreement with our findings in a large sample size.…”
Section: Discussionmentioning
confidence: 98%
“…It participates in food intake, energy balance, lipid and glucose metabolism [13][14][15][16][17][18]. It also influences the hypothalamic-pituitary axis by decreasing serum LH levels and modulating GnRH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The endocannabinoid system contributes to human energy homeostasis and plays a role in lipid and carbohydrate metabolism and also in fat accumulation in liver and muscles [13][14][15][16]. Its key factors are the cannabinoid receptors that are expressed in a variety of tissues including the adipose tissue, liver, skeletal muscle, brain, gastrointestinal tract and pancreas [17].…”
Section: Introductionmentioning
confidence: 99%